(3GdeJHY aj TQM GddeYs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3GHf Lfj , CHh GdaJM YKeGf Hf Lfj GdehUdj, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3bGd GdTjN eMH GdOjf CHh GdHbGA YHO Gddg Hf GdMSjf Hf YHO Gddg Hf GdYcHQi GdfMhi QMeg Gddg aUd ai HjGf GdfMh hGUd hVYg EYde Cf GdfMh ai GdCUd eUOQ fMG jfMh s
(3BNQgG (B:s
(3hCeG GdLeY ajbhd gf aQbhG Hjfg hHjf GdePcQ ceG aQbhG Hjf CfJe hCfJf Je GdLRA GdChd ef GdeJHY ai TQM GddeY aUd hced gPg GdVeGFQ Jchf eQahYI HGdEHJOGA s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1563s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs